A Case of Coexistence of Aplasia Cutis Congenita and Giant Congenital Melanocytic Nevus: Coexistence of Two Rare Skin Diseases - Ping CHEN; Liansheng ZHONG (Chinese Journal of Plastic and Reconstructive Surgery, 2020)
ABSTRACT: Aplasia cutis congenita (ACC) is a rare disease that is characterized by complete or partial absence of skin at birth, either in a localized or widespread region. Melanocytic nevi refers to tumor-like malformations of the skin or mucous membrane caused by benign proliferation of melanocytes. It is classified as a giant congenital melanocytic nevus (GCMN) when the diameter of the largest nevus exceeds 20 cm. The co-occurrence of ACC and GCMN is extremely rare, to the best of our knowledge. We report a case of coexistence of ACC and GCMN of infancy in a 2-month-old male infant. The lesions consisted of a large hyperpigmented plaque occupying most of the trunk and pelvic region, and smaller hyperpigmented plaques on the trunk, head, and extremities. Additionally, there were large, sharply marginated, triangular, depressed atrophic plaques covered by thin, translucent, glistening epithelial membranes in the center of the GCMN on the back. The presumptive diagnosis was coexistence of GCMN and ACC. This could be a manifestation of SCALP syndrome, a rare neuro-cutaneous condition characterized by the presence of Sebaceous nevus, Central nervous system (CNS) malformations, Aplasia cutis congenita, Limbal dermoid and Pigmented (giant melanocytic) nevus.